Social acceptance toward a childcare support robot system: web-based cultural differences investigation and a field study in Japan. (18th July 2017) - Shiomi, Masahiro; Hagita, Norihiro
Abstract: This paper investigates people's social acceptance of a childcare support robot system and compares it with existing childcare technologies (anesthesia during labor and baby food, i.e. processed food and formula milk) through web-based questionnaires between Japan and USA and a field study in Japan. We investigated social acceptance through four scales: intention to use, safety and trustworthiness, negative attitudes, and decreasing workload . For this paper, our participants included 400 people (200 from each country) in Japan and USA located through a web-based survey who answered questionnaires about the four scales to investigate their social acceptance of childcare support technologies. Our web-based survey results indicate that our system's concept was evaluated lower than current childcare support technologies in both Japan and USA. We also conducted a field trial with 30 additional people in Japan and through their actual experiences investigated their evaluations of the prototype of our childcare support robot system. Abstract :